2000
DOI: 10.1016/s0198-8859(99)00134-2
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II haplotype associations with inflammatory bowel disease in Jewish (Ashkenazi) and non-Jewish Caucasian populations

Abstract: Ulcerative colitis (UC) and Crohn's disease (CD) are the clinical entities comprising idiopathic inflammatory bowel disease (IBD). Previous studies on the association of IBD and human leukocyte antigen (HLA) class II genes suggested a role for HLA in this disease. Here we present HLA class II (DRB1, DQB1, DQA1, DPB1) allele and haplotype distributions determined using the polymerase chain reaction and sequence-specific oligonucleotide probe methods. A total of 578 UC and CD Caucasian patients and controls from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 37 publications
4
47
0
Order By: Relevance
“…The up-regulation of antigen presentation genes is consistent with increased expression of HLA Class II molecules that typically occurs in IBD in humans [29]. HLA Class II genes have been associated with risk of IBD in a number of populations [30,31] (reviewed in ref. [32]).…”
Section: Discussionmentioning
confidence: 92%
“…The up-regulation of antigen presentation genes is consistent with increased expression of HLA Class II molecules that typically occurs in IBD in humans [29]. HLA Class II genes have been associated with risk of IBD in a number of populations [30,31] (reviewed in ref. [32]).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated an association between HLA class II alleles and susceptibility to both CD and UC. 27,28 The TNFa locus is a functional and positional candidate gene for IBD, but association studies involving TNFa polymorphisms and IBD have given inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Replicated HLA class Ⅱ associations in IBD include HLA-DRB1*1502 (serological marker HLA-DR2) [76] association with UC, and HLA-DRB1*0103 association with UC and colonic CD [77,78] . HLA-DRB1*0103 is noteworthy in that it is a risk factor for both UC and colonic CD, suggesting it may play a role in chronic inflammation of the colon independent of major IBD phenotype (i.e., CD or UC) [78] .…”
Section: Hla Associationsmentioning
confidence: 99%